Noncovalent Inhibitors of SARS-CoV-2 Main Protease: A Rescaffolding Attempt - Krischuns, Tim; Paisant, Sylvain; Chen, Kuang-Yu; Thirion, Laura N.; Zettor, Agnès; Chiaravalli, Jeanne; Jacob, Yves; Bellinzoni, Marco; Naffakh, Nadia; Janin, Yves L. (Synthesis, 2025)
Out of the results of the sole large-scale screening for inhibitors of SARS-CoV-1 main protease reported in 2013, attempts to improve the identified 3-pyridyl-bearing hits have been conducted in research laboratories, either on this enzyme or more recently on the closely related SARS-CoV-2 main protease. From the resulting structural information reported, we sought to design analogues featuring some of the components providing an affinity for the active site of these proteases along with a different scaffold, which would allow for further structure-activity relationship studies and/or pharmacological improvements. We describe here the introduction of a bridging component with the aim of stabilizing the ligand conformation adopted when bound to these proteases. Accordingly, this led us to prepare 3,3-disubstituted piperazin-2-ones from an array of ketones, via either a Bargellini reaction or a multistage condensation/cyclization/hydrolysis involving ethylene diamine and potassium cyanide. However, even the most elaborate and lipophilic biphenyl-bearing analogues displayed only a weak effect in a bioluminescence-based SARS-CoV-2 main protease inhibition assay.
Keywords: medicinal chemistry; phase-transfer catalysis; SARS-CoV-2 main protease; Bargellini reaction; piperazinone